An interpretive structure modelling of implementation issues for lean manufacturing system. (1st January 2011) - Upadhye, Nitin; Deshmukh, S.G.; Garg, Suresh
In this study, a systemic relationship is developed among lean manufacturing implementation issues, which are identified and supported from various literary sources, using interpretive structural modelling (ISM). ISM provides means to impose order on the complexity of the issues concerned. The decision-makers will be benefited by this model to design a framework to implement LMS. The paper tried to make the mutual influence of LM implementation issues more understandable as well as to identify driving issues (which support other issues) and dependent issues (most influenced by other issues). On the basis of ISM, a model for growth can be developed to gain sustainable competitive advantage.